Hubungan Pengetahuan dan Sikap Terhadap Perilaku Penggunaan Masker dalam Usaha Pencegahan Covid-19 pada Masyarakat Kecamatan Gunung Putri Tahun 2020 - Sukmawati Eka Suhartiningsih (2020)
COVID-19 is a respiratory tract infection caused by Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2). Since its appearance at the end of 2019, COVID-19 cases have continued to increase and their spread has become more widespread. As an effort to prevent COVID-19, the government has socialized the use of masks as an effort to tackle the spread of COVID-19 in Indonesia as a result of WHO recommendations. The purpose of this study was to determine the relationship between knowledge and attitudes in the use of masks as an the effort to prevent COVID-19 in Gunung Putri District community in 2020. This research is a type of analytical study with an observational design and using a cross sectional approach. The sample of this research is 95 respondents. The sampling technique used consecutive sampling with a research instrument, namely google form. Data were analyzed based on the chi-square test. Public attitudes (p = 0.004; 95% CI) had a relationship with mask wearing behavior, while knowledge (p = 0.340; 95% CI) had no relationship with mask wearing behavior. The results showed that there was a significant relationship between attitudes and the behavior of using masks in the efforts to prevent COVID-19 in the people of Gunung Putri District in 2020. To prevent the spread of COVID-19 in Gunung Putri District, the community is expected to continue implementing health protocols in their daily activities.